The Influence of Richeese Customer Preferences on Buying Interest in KFC Which Was Boycotted in Indonesia - Hilya Zulva; Nurul Ifani; Ahmad Nuh; Nur Hasan (CV. Ulil Albab Corp, 2024)
This study aims to analyze the influence of the Richese brand on the dynamics of the KFC boycott in Indonesia, which was triggered by various social and economic factors. The boycott against KFC emerged in response to public reactions to certain issues, during which some consumeSrs switched to other brands that were perceived to align more with their values. One such alternative brand was Richese, which offers similar products in the fast-food category. This research utilized surveys and social media analysis to measure consumer preferences, brand awareness, and the impact on KFC’s sales. The results indicate that the Richese brand experienced a significant rise in popularity during the boycott period, particularly among younger consumers. However, the KFC boycott did not have a lasting impact on KFC's market position in Indonesia, although it did create opportunities for local brands like Richese to expand their market share. The study concludes that boycotts offer alternative brands a chance to capture consumer attention, but the long-term impact depends on other factors such as brand loyalty and product quality.